New Art (New York : Harry N. Abrams Inc. Publishers, 1990)
The art included here is diverse, confirming that many styles still coexist in the art world. We note among recent trends the increasing presence of women artists, the revival of interest in Conceptual Art and Geometric Abstraction, the renewed vigor of Landscape Painting and Political Art, the employment by artists and galleries of installation almost as a medium itself, the broad use of photography and computer-generated imagery, on the one hand, and natural materials, on the other, the appropriation of images from the history of art and popular culture, the fabrication of envionments, and the establishment of a video Foothold in traditional galleries.
Allen, Terry ; Armleder, John ; Bates, David ; Bender, Gretchen ; Bevan, Tony ; Bianchi, Domenico ; Bickerton, Ashley ; Bidlo, Mike ; Bleckner, Ross ; Bloom, Barbara ; Bolande, Jennifer ; Brooks, Ellen ; Bruskin, Grisha ; Burson, Nancy ; Casebere, James ; Cemin, Saint Clair ; Chase, Colin ; Cheng, Ching Ho ; Coe, Sue ; Davis, Debby ; Dibenedetto, Steve ; Dickson, Jane ; Doyle, Katherine ; Drozdik, Orshi ; Dudely, Randy ; Eckart, Christian ; Escobar, Carolina ; Ess, Barbara ; Federle, Helmut ; Fischer, R.M. ; Fisher, Joel ; Frailey, Stephen ; Giegerich, Jill ; Ginder, Robert ; Ginzel, Kristin Jones & Andrew ; Gober, Robert ; Gormley, Antony ; Halley, Peter ; Hardesty, Michael ; Hart, Claudia ; Heino, Steven ; Horn, Rebecca ; Hsu, Tishan ; Innerst, Mark ; Isermann, Jim ; Jaar, Alfredo ; Kabakov, Ilya ; Kapoor, Anish ; Kasten, Barbara ; Kelley, Mike ; Kessler, Jon ; Koons, Jeff ; Kopystiansky, Igor ; Laib, Wolfgang ; Lawler, Louise ; Lemieux, Annette ; Lethbridge, Julian ; Levine, Erik ; Leyba, Orlando Gabino ; Lipski, Donald ; Macaulay, Thomas ; MacDonald, Chris ; Majore, Frank ; Martin, Walter ; Material, Group ; McCollum, Allan ; McDermott & McGough ; Menard, Andrew ; Minter, Marilyn ; Morehead, Gerry ; Mullican, Matt ; Nagy, Peter ; Nechvatal, Joseph ; Neimanas, Joyce ; Nelson, David ; Nelson, Joan ; Oropallo, Deborah ; Otterson, Joel ; Ouattara ; Patkin, Izhar ; Phelan, Ellen ; Prina, Stephen ; Prince, Richard ; Quentel, Holt ; Ray, Charles ; Rollins, Tim & K.O.S. ; Rosler, Martha ; Sciullo, Louis ; Serrano, Andres ; Simmons, Laurie ; Smith, Ray ; Sofer, Ken ; Solano, Susana ; Steinbach, Haim ; stone, William ; Taaffe, Philip ; Trockel, Rosemarie ; Starn, Doug & Mike ; Ukeles, Mierle Laderman ; Vaisman, Meyer ; Viola, Bill ; Webb, Boyd ; Webster, Meg ; Winokur, Neil ; etc.
geboortedatum per kunstenaar
Engels
boek
Keywords: U.S.A.; Amerika; Verenigde Staten van Amerika